2016
DOI: 10.3171/2015.6.jns142483
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of internal carotid artery injuries secondary to endonasal surgery: case series and review of the literature

Abstract: OBJECTIVE Internal carotid artery (ICA) injury is a rare but severe complication of endonasal surgery. The authors describe their endovascular experience managing ICA injuries after transsphenoidal surgery; they review and summarize the current literature regarding endovascular techniques; and they propose a treatment algorithm based on the available evidence. METHODS A retrospective review of 576 transsphenoidal pituitary adenoma resections was performed. Cases of ICA injury occurring at our institution and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 74 publications
1
79
0
Order By: Relevance
“…Whether temporary or permanent repair was attempted endonasally, most reported cases subsequently underwent catheter‐angiography . Angiography was used to determine the degree of injury, adequacy of repair, and determine need for subsequent endovascular or open repair . Although some reported cases showed adequate ICA integrity after endonasal repair, angiography demonstrated a significant rate of ICA pathology .…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether temporary or permanent repair was attempted endonasally, most reported cases subsequently underwent catheter‐angiography . Angiography was used to determine the degree of injury, adequacy of repair, and determine need for subsequent endovascular or open repair . Although some reported cases showed adequate ICA integrity after endonasal repair, angiography demonstrated a significant rate of ICA pathology .…”
Section: Complicationsmentioning
confidence: 99%
“…Angiography was used to determine the degree of injury, adequacy of repair, and determine need for subsequent endovascular or open repair . Although some reported cases showed adequate ICA integrity after endonasal repair, angiography demonstrated a significant rate of ICA pathology . The most common pathology reported as a consequence of endoscopic ICA injury was pseudoaneurysm formation.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Amenta et al 2 reported a case of an iatrogenic ICA pseudoaneurysm that was successfully treated with telescoping PEDs. Sylvester et al 17 presented 2 cases of transsphenoidal pituitary tumor resection with vessel injury treated with PEDs. In both cases, iatrogenic pseudoaneurysms were treated successfully with PEDs without complications, and the patients had good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A Pubmed search for flow diverter placement for treatment of surgical iatrogenic ICA injury revealed eight patients. [4][5][6][7][8][9] Including our case, seven trans-sphenoidal surgeries and two endoscopic sinus surgeries were involved. Angiographic findings include seven pseudo-aneurysms, one extravasation of contrast, and one carotid cavernous fistula (CCF) ( Table 1).…”
Section: Outcome and Follow-upmentioning
confidence: 99%